ChemInform Abstract: Polyfluorides and Neat Fluorine as Host Material in Matrix‐Isolation Experiments. Issue 8 (February 2016) - Brosi, Felix; Vent‐Schmidt, Thomas; Kieninger, Stefanie; Schloeder, Tobias; Beckers, Helmut; Riedel, Sebastian
Abstract: The use of elemental F2 in matrix isolation experiments, purification procedures, and spectroscopic data of fluorine are reported.